A Multilevel Review of Curvilinear Effects on the Creative Work of Teams. (February 2023) - Razinskas, Stefan
Their positive potential often diminishes or even turns negative when antecedents of creativity are taken too far. Despite empirical evidence supporting such curvilinear effects on important outcomes of creative work at the individual and team levels, their theorizing remains rather incomplete, with more attention being paid to explaining the curves' upward rather than downward slopes. By developing a multilevel antecedent-benefit-cost (ABC) framework that synthesizes 120 quantitative-empirical studies on curvilinear effects, this review guides creativity and innovation literature toward conceptual clarity and methodological precision across levels. This is important because the cost-related mechanisms of certain antecedents are still not well understood.